A Meta-Analysis of the Effects of Realistic Mathematics Education-based Teaching on Mathematical Achievement of Students in Turkey - TURGUT, Sedat (Journal of computer and education research, 2021)
The aim of the current study is to determine the effect of realistic mathematics education-based teaching on students' mathematics achievement. For this purpose, a meta-analysis method, which allows combining the results of a series of studies on a subject, was used in the study. A total of 40 scientific publications, 27 thesis and 13 articles, which are suitable for the research problem, were included in the sample of the study. The publications conducted on mathematics achievement in 2020 and earlier in Turkey were used in the study. Process effectiveness method of meta-analysis was employed in the analysis of data and Hedges’s g was used in the calculation of effect size of the study. In determination of the publication bias of the studies included in the meta-analysis, the funnel plot and Rosenthal’s Fail-Safe N-FSN statistics were examined together. In order to determine whether the distribution of the effect sizes is homogenous or not, the results of Q statistic were investigated. As a result, the effect sizes are homogeneously distributed. Therefore, fixed effect model was used. As stated in the fixed effects model, the overall effect size value is 0.760 with a 0.041 level of standard error. As a result of the study, the effect of teaching activities based on realistic mathematics education on mathematical achievement is at a positive medium level. The aim of the current study is to determine the effect of realistic mathematics education-based teaching on students' mathematics achievement. For this purpose, a meta-analysis method, which allows combining the results of a series of studies on a subject, was used in the study. A total of 40 scientific publications, 27 thesis and 13 articles, which are suitable for the research problem, were included in the sample of the study. The publications conducted on mathematics achievement in 2020 and earlier in Turkey were used in the study. Process effectiveness method of meta-analysis was employed in the analysis of data and Hedges’s g was used in the calculation of effect size of the study. In determination of the publication bias of the studies included in the meta-analysis, the funnel plot and Rosenthal’s Fail-Safe N-FSN statistics were examined together. In order to determine whether the distribution of the effect sizes is homogenous or not, the results of Q statistic were investigated. As a result, the effect sizes are homogeneously distributed. Therefore, fixed effect model was used. As stated in the fixed effects model, the overall effect size value is 0.760 with a 0.041 level of standard error. As a result of the study, the effect of teaching activities based on realistic mathematics education on mathematical achievement is at a positive medium level.